The Influence of Love of Money, Machiavellian, and Fraud on Ethical Behavior: A Case Study at The Regional Inspectorate of South Sulawesi Province, Indonesia - Jimmy Makgret; Eva Marin Sambo; Dahniyar Daud (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of Love of Money, Machiavellian traits, and Fraud on the ethical behavior of auditors at the Regional Inspectorate of South Sulawesi Province. Auditors were chosen as the research subjects because they play a strategic role in maintaining the integrity of financial reports and public accountability. This research employs a quantitative approach using questionnaires distributed to auditors, with measurement items developed from each variable’s indicators. The data collected were analyzed using the Statistical Package for the Social Sciences (SPSS) version 27, applying multiple linear regression to test both partial and simultaneous effects among the variables. The results indicate that Love of Money has a positive but not significant effect on auditors’ ethical behavior. Meanwhile, Machiavellian traits have a negative yet insignificant effect, and Fraud also shows a negative but insignificant effect on ethical behavior. Simultaneously, the three independent variables collectively demonstrate a negative direction of influence on ethical behavior, although not statistically significant. These findings suggest that other factors, such as organizational culture, internal control systems, and professional commitment, may play a more dominant role in shaping auditors’ ethical behavior compared to the psychological factors examined. This study is expected to provide theoretical contributions to the development of behavioral accounting literature and practical contributions to strengthening ethical standards for auditors in the public sector.